2018
DOI: 10.1038/s41598-017-18814-9
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Neural Activity in Congenitally Deaf Mice Induced by Infrared Neural Stimulation

Abstract: To determine whether responses during infrared neural stimulation (INS) result from the direct interaction with spiral ganglion neurons (SGNs), we tested three genetically modified deaf mouse models: Atoh1-cre; Atoh1 f/f (Atoh1 conditional knockout, CKO), Atoh1-cre; Atoh1 f/kiNeurog1 (Neurog1 knockin, KI), and the Vglut3 knockout (Vglut3 −/−) mice. All animals were exposed to tone bursts and clicks up to 107 dB (re 20 µPa) and to INS, delivered with a 200 µm optical fiber. The wavelength (λ) was 1860 nm, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 63 publications
0
34
2
Order By: Relevance
“…Their results indicate that the laser needs functional hair cells to stimulate cochlear spiral ganglion neurons; therefore, the method might be applicable only to some types of conductive hearing loss but not to sensorineural hearing loss. Tan et al [20], on the other hand, revealed the laser stimulation could elicit auditory neural activity in congenitally deaf mice, whose cochlea has no synaptic transmission between inner hair cells and spiral ganglion neurons, suggesting that the laser can potentially work as an alternative to the electrical cochlear implant. The idea is partially supported by our data (Fig 1B): the laser stimulation is capable of evoking CAP without causing a measurable CM response.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicate that the laser needs functional hair cells to stimulate cochlear spiral ganglion neurons; therefore, the method might be applicable only to some types of conductive hearing loss but not to sensorineural hearing loss. Tan et al [20], on the other hand, revealed the laser stimulation could elicit auditory neural activity in congenitally deaf mice, whose cochlea has no synaptic transmission between inner hair cells and spiral ganglion neurons, suggesting that the laser can potentially work as an alternative to the electrical cochlear implant. The idea is partially supported by our data (Fig 1B): the laser stimulation is capable of evoking CAP without causing a measurable CM response.…”
Section: Plos Onementioning
confidence: 99%
“…The practical application of this technique has been evaluated using various nervous systems, including the sciatic nerve [8], visual cortex [9], and somatosensory cortex [10]. Cochlear implants are one of the most extensively investigated applications of infrared stimulation [11][12][13][14][15][16][17][18][19][20]. Izzo and colleagues [21] reported that the auditory nerve can be activated by infrared laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in local cell response can be enhanced with another genetic manipulation whereby one Atoh1 allele is replaced by Neurog1 (Atoh1-cre; Atoh1 f / kiNeurog 1 ) . This change rescues the vast majority of IHCs, and many more OHCs (Jahan et al, 2015b ), but functionally, these mice are deaf (Tan et al, 2018 ), demonstrating that we must understand not only the formation of HCs and specific types, but also their complex physical interrelationship and interactions to form the stereotyped radial cellular assembly (Figure 2 ) along with the interplay between development and maintenance required for cell survival and function.…”
Section: Genetic Manipulations Reveal Local Variations In Expression mentioning
confidence: 99%
“…In essence, the organ of Corti provides both a highly stereotyped cellular configuration of two types of mechanosensory hair cells (HCs) surrounded by six distinct supporting cell types, each with unique radial distribution (Jahan et al, 2015a ; Munnamalai and Fekete, 2016 ) and systematic longitudinal (apex to base) local (neighboring cells within the same region of the Organ of Corti) variations (Figure 1 ). While past research has established the functional significance of different mechanotransducting HC types, more recent work has demonstrated that even apparently minor local variations may result in deafness (Tan et al, 2018 ). Ultimately, how global cell type specification and local variation are regulated must be understood for successful regeneration of HCs as a rehabilitation option for deafness (Sha et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 4 Among all neuromodulation techniques, pulsed near-infrared (NIR) radiation (wavelength between 1850 and 2120 nm) is considered a strong candidate for precise control of neural activity, due to its high stimulating spatial resolution and contact-free advantages. 5 10 NIR has been widely used to modulate the functionality of the peripheral 5 7 , 11 , 12 and the central nervous system. 8 10 , 13 , 14 Most previous studies have focused on NIR-induced neural activation; 6 9 , 15 neural suppression is also indispensable in neuroscience, especially for brain disorder treatment.…”
Section: Introductionmentioning
confidence: 99%